Cross-cultural Adaptation and Psychometric Evaluation of the Kurdish Version of the Disabilities of Arm, Shoulder, and Hand (DASH-KU) Scale - Hasan, Rebwar A.; Barawi, Omer A.; Hasan, Jalal A. (Journal of Health and Allied Sciences NU, 2023)
Background The disabilities of arm, shoulder, and hand (DASH) questionnaire addresses the patient's disabilities and symptoms to evaluate the extent and the impact of injuries in the patient's daily-life activities. This study aims to develop a valid and reliable adaptation of DASH into the Kurdish language and culture (DASH-KU).Methods American Association of Orthopedic Surgeons Outcomes Committee guideline was used for the cross-cultural adaptation of DASH to the Kurdish version. This study was conducted at the Shahid Saifaddin consultation clinic in Sulaymaniyah, Iraq between April and October 2022. A total of 300 participants, who were included in the study using an available sampling method, completed the self-report DASH-KU questionnaire during two consecutive assessments with a 24-hour interval.Results The DASH-KU questionnaire demonstrated excellent internal consistency (Cronbach's α = 0.99) and test–retest reliability (intraclass correlation = 0.99). A strong correlation between DASH-KU scores and the patient-rated wrist/hand evaluation tool (r = 0.792) supported its construct validity. Bland–Altman plots showed good agreement between assessments with no floor (3%) or ceiling (0%) effects. Factor analysis found the scale had high adequacy (0.700) and significant sphericity (p < 0.001). The major factor explained 40% of variance with an eigenvalue of 13.14. Additionally, a five-item model explained 81.23% of DASH-KU variance, though responsiveness was suboptimal, possibly due to the short 24-hour interval between measurements.Conclusion Our results demonstrate that DASH-KU has excellent reliability and validity in identifying upper limb injuries, and the psychometric properties of DASH-KU were similar to its original version.
Keywords: upper limb conditions; reliability and validity; patient-reported outcome measures; self-report